Analisis Kredit Macet dalam Menentukan Kebijakan Restrukturisasi - Ibnu Hadi Bidja; Sahmin Noholo; Nilawaty Yusuf (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to find out how bad credit is resolved by credit restructuring at BRI Central Unit. This research uses descriptive qualitative research methods. The data source used in this research is primary data obtained from interviews and secondary data obtained from the agency, namely Bank BRI Central Unit. Data collection methods were carried out using observation, interviews and documentation methods. Based on the research results, it shows that resolving bad credit or problematic credit in the BRI Central Unit implements a restructuring policy as an effective and efficient way to reduce the level of bad credit. BRI Central Unit creditors have carried out credit restructuring in accordance with applicable banking laws and internal bank regulations. In settlement using the restructuring method, the creditor adheres to the conditions issued by BI, in accordance with the provisions regarding credit restructuring was first regulated in Bank Indonesia Directors’ Decree No. 31/150/KEP/DIR dated 12 November 1998 concerning Credit Restructuring which was later changed to Bank Indonesia Regulation No. 2/15/PBI/2000 concerning Credit Restructuring